PERSONAL BOUNDARIES AND PSYCHOLOGICAL WELLNESS OF CAPIZ COMMERCIAL SCHOOL STUDENTS - Rosemarie, Late; Lynn, Siglos Caressa; Emmylou, Ciudadano (President University, 2024)
This study aimed to assess the degree of personal boundaries and the level of wellness among students of Capiz Commercial School. A sample of 159 students from intermediate, junior high, and senior high schools was randomly selected as respondents for the study. The researcher collected the data from randomly selected respondents using a validated and reliability-tested research-made questionnaire. The data were analyzed and interpreted using statistical tools such as frequency count, percentage, mean, t-test, f-test, Analysis of Variance, and Pearson-r. The study found moderate personal boundaries in students, showing that they spend time with others without being overly dependent or isolated. The subscale psychological boundaries were high, indicating that respondents have strong emotional independence. The moderate physical boundaries indicate that the students are comfortable initiating physical contact and obtaining permission from others to do so. High mental health was reported. Self- and social-relationships were also good. When considering sex, age, grade level, and family income, personal boundaries varied significantly. Family income alone considerably influenced the level of psychological wellness. Finally, there was no significant relationship between students' personal boundaries and psychological wellness, indicating that it is unlikely to impact them. Nevertheless, it is imperative to acknowledge the limitations of the research, acknowledge individual differences, and acknowledge that the absence of a statistical relationship does not diminish the significance of personal boundaries in individual cases.